2016
DOI: 10.1080/02640414.2016.1271138
|View full text |Cite
|
Sign up to set email alerts
|

Increasing hip and knee flexion during a drop-jump task reduces tibiofemoral shear and compressive forces: implications for ACL injury prevention training

Abstract: Although most ACL injury prevention programmes encourage greater hip and knee flexion during landing, it remains unknown how this technique influences tibiofemoral joint forces. We examined whether a landing strategy utilising greater hip and knee flexion decreases tibiofemoral anterior shear and compression. Twelve healthy women (25.9 ± 3.5 years) performed a drop-jump task before and after a training session (10-15 min) that emphasised greater hip and knee flexion. Peak tibiofemoral anterior shear and compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…In our study, although there were no changes in hip or ankle angles due to match play, there was a 12.8% increase from baseline in knee flexion at T3. Based on existing literature, increased knee flexion during landing is desirable, since it can improve the mechanical advantage of the knee flexors, aiding the ACL in resisting potential anterior tibial shear [39]. However, in the current study, the decrease in KF strength at T3, combined with a recovery of KE strength to baseline levels and the small effect size (0.398) of the knee angle change, make a potential protective effect less likely.…”
Section: Discussionmentioning
confidence: 82%
“…In our study, although there were no changes in hip or ankle angles due to match play, there was a 12.8% increase from baseline in knee flexion at T3. Based on existing literature, increased knee flexion during landing is desirable, since it can improve the mechanical advantage of the knee flexors, aiding the ACL in resisting potential anterior tibial shear [39]. However, in the current study, the decrease in KF strength at T3, combined with a recovery of KE strength to baseline levels and the small effect size (0.398) of the knee angle change, make a potential protective effect less likely.…”
Section: Discussionmentioning
confidence: 82%
“…Although Paterno et al focused on limb asymmetry after ACLR for the risk of secondary injury, they recommended for an attempt to decrease residual limb asymmetries that clinicians should consider incorporating similar principles of ACL injury prevention into the late stages of ACLR rehabilitation 20,33 . For reducing VGRF or joint moment, Tsai et al reported increasing range of motion of hip and knee flexion reduced tibiofemoral shear and compressive forces 34 . Moreover, DiStefano et.al.…”
Section: Discussionmentioning
confidence: 99%
“…This gender difference seems to emerge during maturation, where post-pubertal girls are noted to land with more extended knee joint angles compared to pre-pubertal girls ( DiStefano et al, 2015 ). Use of extended knee joint positions during landing has been associated with elevated anterior shear forces in the knee joint and hence presumably elevated ACL strain in female study participants ( Chappell et al, 2002 ; Shultz et al, 2009 ; Tsai and Powers, 2013 ; Tsai et al, 2017 ). Likewise, computer model analysis of landings have uniformly indicated that landing/cutting at more extended hip and knee joint angles are predictive of elevated anterior tibial shear forces most likely resulting in increased strain in the ACL ( Sell et al, 2007 ; Southard et al, 2012 ; Tsai and Powers, 2013 ; Tsai et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Use of extended knee joint positions during landing has been associated with elevated anterior shear forces in the knee joint and hence presumably elevated ACL strain in female study participants ( Chappell et al, 2002 ; Shultz et al, 2009 ; Tsai and Powers, 2013 ; Tsai et al, 2017 ). Likewise, computer model analysis of landings have uniformly indicated that landing/cutting at more extended hip and knee joint angles are predictive of elevated anterior tibial shear forces most likely resulting in increased strain in the ACL ( Sell et al, 2007 ; Southard et al, 2012 ; Tsai and Powers, 2013 ; Tsai et al, 2017 ). Conversely, landing or sidecutting with more flexed knee joint angles has been reported to reduce the magnitude of anteriorly directed strain in the ACL, but also to facilitate the hamstrings to act as ACL synergists as demonstrated in cadaveric studies and using computer modeling ( Li et al, 1999 ; Kernozek and Ragan, 2008 ; Southard et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%